Pengaruh Literasi Ekonomi, Kontrol Diri, dan “FOMO”, terhadap Pembelian Impulsif pada Generasi Milenial - Nurjanah, Siti; Sadiah, Ati; Gumilar, Rendra (Global Education Journal, 2023)
The purpose of this study was to measure the extent to which economic literacy, self-control and fomo influence the impulsive buying of the millennial generation. This study uses the quantitative survey type method with an explanatory design. After making observations at the research location in Sawati Village, there was a problem of a difference between knowledge and actions of millennials who consider impulsive buying trivial. The research location that I choose has never been even rarely investigated by previous studies and this phenomenon does not occur in all regions. The data collection method is using a questionnaire and the analytical tool used is SPSS version 23, then before the questionnaire is distributed, the instrument will be tested for validity and reliability. The populations are millennials who live in Sawati Village with an age range 21 to 40 years old with a total sample of 125 respondents. Data analysis techniques using the classical assumption test (normality test, reliability test, multicollinearity test, and heteroscedasticity test), multiple linear regression, hypothesis testing (t test and F test), and the coefficient of determination (R square). The findings of this study partially namely economic literacy has no effect on impulsive buying, self-control and fomo have an effect on impulsive buying, then simultaneously economic literacy, self-control and fomo has a significant effect on impulsive buying and in accordance with the grand theory of Kotler 2016. The practical implications of this study are that they can help develop understanding of the phenomenon under study. Both for practitioners, decision makers, and related parties. Provide guidance and recommendations to practitioners in developing policy strategies or best practices in relevant fields, in this case consumer behavior.